Impact of electronic vaccine intelligence network application used in immunization sessions in Pune city - Mahanubhav, Damini S.; Salunke, Nandkumar M.; Shelke, Sangita C.; Parande, Malangori A.; Tambe, Muralidhar P. (International Journal Of Community Medicine And Public Health, 2021)
Background: Millions of deaths due to various diseases have been reduced globally as well as in India since inception of vaccination programme. In order to avoid the instances of cold chain failure and ensure constant monitoring of temperature of cold chain equipment’s Electronic vaccine intelligence network (eVIN) technology was adopted by Government of India. Methods: A mixed methodology design with both qualitative as well as quantitative components were studied. This study was conducted in 16 immunization centres spread across the metropolitan Pune city in western Maharashtra. Results: Vaccine beneficiaries increased for polio 814 (3.25%), DPT1643 (21.79%), MR 9615 (23.02%) and IPV 2297 (23.58) vaccine after execution of eVIN app. Vaccine availability of BCG (6.04%), Polio (20.02%), MR (64.24%), IPV (11.38%) and hep B had increased as compared to the other vaccines. The vaccine wastage decreased for penta (8.64%), IPV (123.98%), TT (32.63%) and hep B (47%) vaccines post eVIN application compared to the pre eVIN. The qualitative study included in depth interviews, key informants’ interview and focus group discussions. Various themes and subthemes emerged like the user-friendliness of app, difficulties faced by health care workers, their suggestions for improvements in the app. Conclusions: The eVIN system is playing a pivotal role in effective and efficient management of vaccine supply, maintaining stock availability and monitoring. To reduce vaccine wastage usage of small dose vials in immunization sessions would be helpful.